PPO.58 Outcome of Pregnancy with Low PAPP-A. (9th June 2014) - Imcha, M; Egbase, E; Ross, G
Abstract : Background: PAPP-A is a biochemical marker in first trimester screening undertaken at 11–13 weeks gestation. Studies have shown that low levels of it (<0.4 MoM) are descriptive of poor early placentation and can be an independent risk factor of complications associated with adverse obstetric outcomes. Objective: Review existing management and pregnancy outcome of women with low PAPP-A levels and formulate guidelines to establish uniform standard practice for better outcomes. Method: Following parameters were retrospectively analysed from case notes from January to December 2011: Maternal Age Parity Miscarriage PAPP-A levels Aspirin Uterine artery Doppler Growth scan Hypertension Delivery time Stillbirth APGAR SCBU admission Results: 81 identified with low PAPP-A 90% received counselling 46% commenced on low dose aspirin 88% had uterine artery doppler 75% had growth scans 66% had no growth restriction 66% had further dopplers 38% received steroids 64% had no adverse outcomes 60% of babies born had weight greater than 3kg 25% had SCBU admission 36% had adverse outcomes Conclusion: Low PAPP-A levels have limited value as a one-time single marker test and is poorly sensitive. Likelihood of an adverse outcome increases as PAPP-A level decreases. For pregnant women with a low PAPP-A level, monitoring of fetal growth and doppler indices can help identify high risk of adverse obstetric outcomes. Even if the ultrasound examination is normal it does not rule out an adverse outcome. Increased surveillance during pregnancy and low dose aspirin with uterine artery doppler were introduced in the guidelines for management of pregnant women with low PAPP-A.